Scoping Review: Factors Influencing Cyber-Aggression Of Adolescents In The Digital Era - Febryana Utami Aras; Annastasia Ediati (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
The advancement of technology has led to the increasing popularity of social media across all ages in this digital era due to its diverse benefits in daily life. Notably, 60% of social media users are adolescents. Emotional instability in adolescents frequently gives rise to developmental issues, including behavioral problems such as aggression. A prominent behavioral issue emerging in this digital age is online aggressive behavior, commonly referred to as cyber-aggression. Prior research has demonstrated that adolescents active on social media have engaged in cyber- aggression. This study aims to identify the factors influencing cyber-aggression behavior among adolescents in the digital era. The research design employed is a scoping review. Articles were searched using three databases: Scopus, SpringerLink, and Semantic Scholar. The initial search yielded 10.176 articles, and subsequent screening based on inclusion criteria resulted in 6 eligible articles. The review findings indicate risk and protective factors. Risk factors that come from adolescent’s personal include such as cyber moral disengagement, tendency to worry about others' thoughts and opinions, aggression traits, and also the level of adolescents' perception of threat. Situational factors include such as authoritarian parenting, level of internet exposure, and the amount of time adolescents spend on the internet. While protective factors, identified come from adolescent’s microsystem, such as parents, peers and school climate. Further research is warranted to investigate spesifically the potential protective factors to mitigate cyber-aggression among adolescents in the digital era.